2021
DOI: 10.1039/d1cb00079a
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the substrate recognition mechanisms of the heparan sulfate 3-O-sulfotransferase-3

Abstract: The sulfation at the 3-OH position of a glucosamine saccharide is a rare modification, but is critically important for the biological activities of heparan sulfate polysaccharides. Heparan sulfate 3-O-sulfotransferase (3-OST),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…3-OST-5 can generate 8-mers both with and without anticoagulant activity, depending on the saccharide sequences around the 3- O -sulfation site. Compared with previously published structures of 3-OST-1 and 3-OST-3, we discovered that 3-OST-5 has a very similar structure in the active site and overall structure to 3-OST-1 and 3-OST-3. We also determined that the substrate specificity of 3-OST-5 is not only governed by the side chains from amino acid residues in the active site but also by uronic acids flanking both sides of the acceptor.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…3-OST-5 can generate 8-mers both with and without anticoagulant activity, depending on the saccharide sequences around the 3- O -sulfation site. Compared with previously published structures of 3-OST-1 and 3-OST-3, we discovered that 3-OST-5 has a very similar structure in the active site and overall structure to 3-OST-1 and 3-OST-3. We also determined that the substrate specificity of 3-OST-5 is not only governed by the side chains from amino acid residues in the active site but also by uronic acids flanking both sides of the acceptor.…”
supporting
confidence: 50%
“…For the first time, we solved the structures of 3-OST-5 in complex with oligosaccharide substrates. Comparing the crystal structures of 3-OST isoforms 1, 3, and 5 with substrate bound, , we found that the active sites are very similar, although subtle structural differences exist. To our surprise, we discovered that the presence of IdoA2S reduces the reactivity of 3-OST-5 for modification.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…They exist in numerous isoforms with varying substrate preferences. 18 The sulfated products of this reaction play important roles in cell communication 19 and also feature in various pathologies including those of cancer, 20 Alzheimer's 21 and the mucopolysaccharidoses. 22 Heparan sulfotransferases belong to the wider group of sulfotransferases found across nature that use the universal sulfate donor compound PAPS (adenosine-3′-phosphate-5′-phosphosulfate), 23 and produce PAP (adenosine-3′,5′-diphosphate) as a by-product ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%